(untitled) (CR. Conservación y Restauración, 2025)
Illicit trafficking of cultural property is portrayed and acknowledged in International Cultural Heritage Law. In Mexico, despite not being an offense, the actions that constitute it are sanctioned by means of the crimes contained in the Ley Federal sobre Monumentos y Zonas Arqueológicos, Artísticos e Históricos (LFMZAAH). When the theft, looting or illicit transfer of cultural property occurs, the conservation of the objects and the information about the past of humanity they withhold is put at risk. Illicit trafficking is not a new problem, it is one that persists in humanity’s contemporary history. Being a collective action problem, it requires a response from the international community as a whole. In this sense, each State must promote the protection of the heritage that it safeguards within its territory, through lawmaking and the implementation of public policies. It is also the responsibility of each government to take measures to prevent the entrance of cultural assets from other countries into their borders and for them to be placed in the international market. Mexico is not exempt from that reality. A national policy on the matter is needed to prevent it and achieve the recovery of the affected objects.